A new Phymaturus species from volcanic Cordilleran mountains of the south-western Mendoza Province, Argentina (Liolaemidae, Iguania, Lacertilia, Reptilia) - Cei, José Miguel Alfredo María (2003)
A new liolaemid species of the genus Phymaturus is described and discussed. The only known sample comes from the Peteroa Volcano mountains (about 2000 m a.s.l.), close to the Chilean frontier in the Andean region of Southern Mendoza province, Argentina. Its relationships with all Phymaturus species recognized from Chile and Argentina are analyzed. Beside the peculiar morphological and chromatic characters of this stout lizard, its different karyotypic number and composition is pointed out.